Which Hebrew Bible? Review of Biblia Hebraica Quinta, Hebrew University Bible, Oxford Hebrew Bible, and Other Modern Editions - Baker, David Leslie (Tyndale bulletin, 2010)
Three major critical editions of the Hebrew Bible/Old Testament are in preparation at present: Biblia Hebraica Quinta (BHQ), the Hebrew University Bible (HUB), and the Oxford Hebrew Bible (OHB). This article is a comparative review of these three editions, followed by a briefer review of six other modern editions: British and Foreign Bible Society (BFBS), NIV Interlinear Hebrew-English Old Testament, Jewish Publication Society (JPS), Jerusalem Crown (JC), Biblia Hebraica Leningradensia (BHL), and the Reader’s Hebrew Bible (RHB). Finally, there is a brief discussion of implicit editions and electronic editions, followed by concluding remarks on the usefulness of the various editions.